2007
DOI: 10.1056/nejmoa065733
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized Trial of Prophylactic Fluconazole in Preterm Neonates

Abstract: Prophylactic fluconazole reduces the incidence of colonization and invasive candida infection in neonates weighing less than 1500 g at birth. The benefit of treating candida colonization is unclear. (Current Controlled Trials number, ISRCTN85753869 [controlled-trials.com]).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
201
6
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(219 citation statements)
references
References 34 publications
6
201
6
6
Order By: Relevance
“…7,[9][10][11][12]14,15,18 In solid organ and bone marrow transplant patients, antifungal prophylaxis with fluconazole has been successfully used for years to prevent colonization and infection due to Candida species and markedly reduced the need for empiric amphotericin B therapy. 19,20 However, because of the lack of larger multicenter randomized trials and data on long-term Fluconazole prophylaxis for highest risk infants J-H Weitkamp et al neurodevelopmental outcomes as well as concerns about unwanted side effects and development of Candida resistance, fluconazole prophylaxis in high-risk infants remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[9][10][11][12]14,15,18 In solid organ and bone marrow transplant patients, antifungal prophylaxis with fluconazole has been successfully used for years to prevent colonization and infection due to Candida species and markedly reduced the need for empiric amphotericin B therapy. 19,20 However, because of the lack of larger multicenter randomized trials and data on long-term Fluconazole prophylaxis for highest risk infants J-H Weitkamp et al neurodevelopmental outcomes as well as concerns about unwanted side effects and development of Candida resistance, fluconazole prophylaxis in high-risk infants remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In contrast, many other studies did not find a difference in overall mortality, 7,9,12-14 including a recent multicenter trial. 15 Concerns about development of azole resistance and unwanted drug side effects remain. One study reported an association between fluconazole use and a higher incidence of cholestasis.…”
Section: Introductionmentioning
confidence: 99%
“…In this trial, having two or more sites positive in a single day was associated with an odd ratio of 8.2. Recently, Manzoni et al [11] showed a significant decrease of invasive candidiasis with fluconazole prophylaxis, although this was in neonates; no effect on mortality was observed.…”
Section: Prophylactic Antifungal Treatment In the Icumentioning
confidence: 99%
“…Colonization at multiple sites and CVC colonization have been reported as independent risk factors for candidal BSI [100]. The use of fluconazole prophylaxis seems to be effective against fungal colonization as well as to prevent candidal BSI [91][92][93][94][95][101][102][103]. None of the prophylaxis studies has reported changes in the fluconazole susceptibility of the Candida strains.…”
Section: Bloodstream Infectionsmentioning
confidence: 99%
“…The attack rate of invasive Candida infections over the past two decades has ranged from 3% to 17% among VLBW infants, and from 6% to 20% among extremely low birth weight infants (≤1,000 g), with a case-fatality of around 30% [10,[86][87][88][89][90][91][92][93][94][95]. The main causative agents causing candidemias in the VLBW infant population have been Candida albicans and Candida parapsilosis, and a shift towards the latter has occurred gradually [86,96,97].…”
Section: Bloodstream Infectionsmentioning
confidence: 99%